GOODS DELIVERY SYSTEM DESIGN PT.JASA PRATAMA - Mia Syafira; Yuce Yulina, SKom, MM (Jurnal Sistem Informasi, 2002)
In this study, the authors take the title "delivery system design on PT.Jasa Pratama". Where delivery is sala one of the major activities of the company. For the delivery of processing performed by data entry and to facilitate the delivery process is done with computer processing. Therefore, the authors use the programming language Visual Basic version 6.0 for the system in the company shipping the goods will be processed efficiently and improve the information produced.